Coordinated Logistics with a Truck and a Drone - Carlsson, John Gunnar; Song, Siyuan (Management Science, 2018)
We determine the efficiency of a delivery system in which an unmanned aerial vehicle (UAV) provides service to customers while making return trips to a truck that is itself moving. In other words, a UAV picks up a package from the truck (which continues on its route), and after delivering the package, the UAV returns to the truck to pick up the next package. Although the hardware for such systems already exists, the extent to which such an approach can actually provide a significantly improved quality of service is not yet understood. By combining a theoretical analysis in the Euclidean plane with real-time numerical simulations on a road network, we demonstrate that the improvement in efficiency is proportional to the square root of the ratio of the speeds of the truck and the UAV. The online supplement is available at https://doi.org/10.1287/mnsc.2017.2824 . This paper was accepted by Vishal Gaur, operations management.